Outcomes of childhood conduct problem trajectories in early adulthood: findings from the ALSPAC study. - Kretschmer, Tina; Hickman, Matthew; Doerner, Rita; Emond, Alan; Lewis, Glyn; Macleod, John; Maughan, Barbara; Munafò, Marcus; Heron, Jon (European Child & Adolescent Psychiatry, 2014)
Although conduct problems in childhood are stably associated with problem outcomes, not every child who presents with conduct problems is at risk. This study extends previous studies by testing whether childhood conduct problem trajectories are predictive of a wide range of other health and behavior problems in early adulthood using a general population sample. Based on 7,218 individuals from the Avon longitudinal study of parents and children, a three-step approach was used to model childhood conduct problem development and identify differences in early adult health and behavior problems. Childhood conduct problems were assessed on six occasions between age 4 and 13 and health and behavior outcomes were measured at age 18. Individuals who displayed early-onset persistent conduct problems throughout childhood were at greater risk for almost all forms of later problems. Individuals on the adolescent-onset conduct problem path consumed more tobacco and illegal drugs and engaged more often in risky sexual behavior than individuals without childhood conduct problems. Levels of health and behavior problems for individuals on the childhood-limited path were in between those for stable low and stable high trajectories. Childhood conduct problems are pervasive and substantially affect adjustment in early adulthood both in at-risk samples as shown in previous studies, but also in a general population sample. Knowing a child's developmental course can help to evaluate the risk for later maladjustment and be indicative of the need for early intervention.